Alaska as an example of tourist reception area - Papińska, Elżbieta (Acta Universitatis Lodziensis. Folia Geographica Physica, 2013)
The State of Alaska is located in the north-western North America. Its area of 1 717 854 km2 is populated by 731 449 people (as 2012). Population density is low, only 0.5 person per square km. The main reason for the low population density are unfa-vourable natural conditions, the most important of which include climate, permafrost and topography. Alaska’s landscape diversity is a consequence of the variety of terrain types. For that reason, there are 8 national parks (Denali National Park, Gates of the Arctic National Park, Glacier Bay National Park, Katmai National Park, Kenai Fjords National Park, Kobuk Valley National Park, Lake Clark National Park, Wrangell-St. Elias National Park), national monuments and other lower rank protected areas established in Alaska. Each of these places, characterized by unique types of landscape (for example: glaciers, active volcanoes, fjords, high mountains) brings millions of tourists per year from the USA and all over the world. All these protected areas are very important for the development of tourist industry, and thus for the economy of USA. Alaska’s national parks draw about 2 million visitors annually. Stan Alaska położony jest na północnym-zachodzie Ameryki Północnej. Zajmuje on 1 717 854 km2 powierzchni, którą zamieszkuje 731 449 mieszkańców (2012 r.). Gęstość zaludnienia jest niewielka i wynosi zaledwie 0,5 os/km2. Wpływ na tę sytuację mają przede wszystkim stosunkowo niekorzystne warunki naturalne, z których najważniejszy wpływ mają warunki klimatyczne, wieloletnia zmarzlina i ukształtowanie terenu. Różnorodność krajobrazu będąca efektem ogromnego zróżnicowania form rzeźby, zdecydowała, iż na terenie Alaski utworzono 8 parków narodowych (Denali National Park, Gates of the Arctic National Park, Glacier Bay National Park, Katmai National Park, Kenai Fjords National Park, Kobuk Valley National Park, Lake Clark National Park, Wrangell‒St. Elias National Park), utworzono pomniki narodowe oraz obszary o niższej randze ochrony. Każdy z tych obszarów stanowi magnes przyciągający rzesze turystów z USA i z całego świata, gdyż znajdują się tu niepowtarzalne formy krajobrazu, jak lodowce, aktywne wulkany, fiordy, wysokie góry. Obszary te mają ogromne znaczenie dla rozwoju turystyki w USA, a tym samym dla gospodarki. Rocznie tylko Alaskę odwiedza ok. 2 mln osób.